PENGARUH INFLASI, SUKU BUNGA, PERTUMBUHAN EKONOMI DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR Di BURSA EFEK INDONESIA PERIODE 2019-2023 - Silalahi, Esli; Simanihuruk, Elsa; Silalahi, Donalson (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
This research aims to determine and analyze the influence of inflation, interest rates, economic growth and exchange rates on share prices in banking companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The population in this research is 47 banking companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling technique used was purposive sampling, so that 27 banking companies were obtained with a research period of 5 years. The data analysis technique used is multiple linear regression analysis and descriptive statistical analysis. Hypothesis testing uses the t test and F test with a significance level of 5%. The research results show that partially, inflation has a negative and insignificant effect on banking company share prices, interest rates have a negative and significant effect on banking company share prices, economic growth has a positive and insignificant effect on banking companies, and the exchange rate has a positive and significant effect on prices. banking company shares. Simultaneously inflation, interest rates, economic growth and exchange rates have a significant effect on banking company share prices. The value of share prices can be explained by inflation, interest rates, economic growth and exchange rates by 0.117 or 11.7% as shown by the R-square results.